Landform boundary effects on Holocene forager landscape use in arid South Australia. (June 2018) - Marwick, Ben; Hiscock, Peter; Sullivan, Marjorie; Hughes, Philip
Abstract: Landscapes throughout any region vary in the resources they contain. We investigate how Holocene forager populations adapted to this variation in a linear sand dune desert of arid South Australia. We use data from surface scatters of stone artefacts collected during pedestrian survey to compare behaviours at landform boundaries to behaviours at the centers of landforms. We propose a model of human use of the landscape that predicts the prehistoric occupants of the study were sensitive to the different economic potential of subtly dissimilar landscapes. In evaluating the model we find that there are different densities of archaeological sites in each landscape type. We also find indications of a boundary effect resulting from people having used marginal areas of each landscape type in response to the resource characteristics of adjoining landforms. In addition, we make some observations on our field data collection methods, identifying the general conditions where mobile GIS may be optimally efficient for archaeological survey. Highlights: A large dataset of surface sites from the Australian arid zone is described. Data collected by mobile GIS was more efficient than when collected on paper. Variation in past human land use form gradients relative to landform boundaries. Boundary effects occur in marginal areas in response to adjoining landforms. Human forager populations were sensitive to subtly dissimilar arid landscapes.